A two-level topological model for 3D features in CityGML. (September 2016) - Li, Lin; Luo, Feng; Zhu, Haihong; Ying, Shen; Zhao, Zhigang
Abstract: CityGML, as the standard for the representation and exchange of 3D city models, contains rich information in terms of geometry, semantics, topology and appearance. With respect to topology, CityGML adopts the XLink approach to represent topological relationships between different geometric aggregates or thematic features; however, it is limited to shared objects. This paper proposes a two-level model for representing 3D topological relationships in CityGML: high-level (semantic-level) topology between semantic features and low-level (geometric-level) topology between geometric primitives. Five topological relationships are adopted in this model: touch, in, equal, overlap and disjoint . The semantic-level topology is derived from the geometric-level topology on the basis of the shared geometric primitives. To maintain the 3D topology, topological consistency rules are presented. An Application Domain Extension, called TopoADE, is proposed for the implementation of the topological model. The TopoADE consists of three modules: Topology, Feature and Geometry. Finally, 3D city models with LoD1 to LoD4 are used to test this model. Experimentation on those data sets indicates a validation of the proposed topological model in CityGML. Highlights: Proposed a two-level topological model for 3D features in CityGML: semantic-level topology and geometric-level topology Proposed extended rules of topological consistency to guarantee the validation of primitives in 3D city models Incorporated the topological model in CityGML via an ADE mechanism Validated the topological model among LoDs in CityGML